2020
DOI: 10.3390/ani10030506
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Transient Receptor Potential Vanilloid 1 (TRPV1) in Equine Articular Tissue

Abstract: Joint pain and osteoarthritis (OA) are some of the most common causes of lameness in horses, and most of the available treatments focus on symptomatic relief without a disease-modifying effect. TRPV1 is a potential target for treating joint diseases, including OA, and the present study aims to investigate if the TRPV1 receptor is present in equine articular tissue and determine whether the number of receptors is upregulated in joint inflammation. Metacarpo/metatarsophalangeal (MCP/MTP) joints from 15 horses eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…To date, the gene expression has been reported in the equine synovial membrane only for TRPV1 (4). The present study confirmed the expression of TRPV1 and also demonstrated the expression of Cnr1, Cnr2, GPR55, and PPARA, according to the Authors' protein data.…”
Section: Cnr Cnr Gpr Trpv and Ppara Gene Expression In Synoviocytessupporting
confidence: 86%
See 2 more Smart Citations
“…To date, the gene expression has been reported in the equine synovial membrane only for TRPV1 (4). The present study confirmed the expression of TRPV1 and also demonstrated the expression of Cnr1, Cnr2, GPR55, and PPARA, according to the Authors' protein data.…”
Section: Cnr Cnr Gpr Trpv and Ppara Gene Expression In Synoviocytessupporting
confidence: 86%
“…The metacarpophalangeal joint is a high mobility structure which undergoes enormous loading during locomotion and jumping in the horse (1), so much so that it is the most commonly reported joint affected by traumatic and degenerative lesions in equine athletes (2) and results in lameness in thoroughbred racehorses (3,4). Currently, there is no specific cure for joint disease, and the multimodal pharmacological treatment does not act on the cause of joint inflammation but is aimed at slowing its progression, minimizing/reducing pain, and increasing function and performance (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A previous study reported that the total protein levels of TRPV1 in osteoarthritis (OA) were higher than those found in healthy joints. 6 ASIC3 is a sodium-selective ion channel activated by low extracellular pH and a member of the degenerin sodium channel superfamily. It is a pain modulator expressed in the knee joint, strongly correlated with weight-bearing pain and secondary hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, AEA may interact and activate other targets, such as the transient receptor potential vanilloid type 1 (TRPV1) [ 15 ]. TRPV1 was originally reported to be expressed on the peripheral nociceptive afferents and is present in the spinal and supraspinal structures [ 16 ]; TRPV1 is also expressed in multiple cell types of the joint [ 17 , 18 , 19 ]. Interestingly, a variant of the TRPV1 gene is associated with the risk of the development of symptomatic OA [ 20 ].…”
Section: Introductionmentioning
confidence: 99%